PENGARUH APLIKASI HASIL SAMPING INDUSTRI RUMPUT LAUT TERHADAP SIFAT KIMIA TANAH DAN PERTUMBUHAN TANAMAN JAGUNG - Rahmat Satriya; Bambang Siswanto; Yulia Nuraini (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2016)
Improvement of soil productivity can be made by application of organic waste. Ne of organic wastes having potential to be used as organic materials is seaweed industry waste. The objective of this study was to find out the effects of application of seaweed industry waste on chemical properties of an Inceptisol and growth of maize. Treatments tested in this study were P1= Urea 100kg ha-1, KCl 100 kg ha-1; P2 = P1 + seaweed industry waste 5 t ha-1; P3 = P1 + seaweed industry waste 10 t ha-1; and P4 = P1 + seaweed industry waste 15 t ha-1.Maize seeds were grown for 45 days. The results showed that application of seaweed industry waste affected soil chemical properties (pH, Â C organic, available P, available K, and available K) nutrients uptake by maize (N, P and K uptake), and maize growth.